Weight Changes in Bali Cattle During Lactation at Different Seasons in the Cattle-Oil Palm Production System - Maulana, Hamdani; Panjono, Panjono; Budisatria, I Gede Suparta; Widayati, Diah Tri; Atmoko, Bayu Andri; Baliarti, Endang (Universitas Bengkulu, 2023)
The season impacts livestock productivity and cattle kept in grazing production systems in tropical conditions. This research aims to determine the effect of season on the weight changes of Bali cows and calves on oil palm plantations. This research used 20 Bali cattle kept semi-intensively in oil palm plantation areas without feed supplementation in 2016–2018. Cows and calves were weighed at calving and every month until weaning (150 days). Season grouping was based on calving time: dry season (DS) May–October and rainy season (RS) November–April. Data were analyzed by independent T-test statistics using the SPSS 20.0 application. The results of observations showed that cows' body weight decreased gradually until the fourth month of lactation in both seasons. Cows' weight changes were only significantly different in the second month, in which cows at DS were better than RS (P<0.05). The pre-weaning average daily gain (ADG) of calves each month was not significantly different between the two seasons, and they could reach a body weight of 60.60 kg (RS) and 61.47 kg (DS) at weaning. Season differences do not impact weight changes in the Bali cows and calves in the cattle-oil palm plantation production system.